Optimalisasi Pendampingan Penulisan Karya Ilmiah Berbasis Platform SMILE untuk Pegawai Bapas Kelas I Cirebon - Eha Julaeha; Herny Novianti; Nurhannah Widianti; Ade Hidayat; Ilham Athallah Luthfi; Qurrota Ayun (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2024)
The PkM aims to improve the skills of JFT Bapas Class I Cirebon employees in writing scientific papers and motivate them to publish. The PkM activity applies the concept of self learning (SL). This is a strategic effort to build a mentoring atmosphere that is creative and innovative. There are four phases that need to be done by service providers: investigation, preparation, action, and reflection. Referring to this explanation, the scientific writing consultation service at Bapas Class I Cirebon was transformed into a technology-based one. The PkM mentoring at Bapas Class I Cirebon was held at the Bapas Class I Cirebon hall on November 16-17, 2023 and continued online. Participants included 18 JFT employees. The PkM was opened by the Head of Bapas Class I Cirebon, Rony Kurnia, and went smoothly and conducively. The Head and Participants of Bapas Class I Cirebon positively welcomed this platform-based mentoring. This makes it easier for employees to access repeatedly. The mentoring utilizes the smile platform designed by the writing team with a project-based method and based on the needs of JFT employees. Through this method, the mentoring is carried out on an ongoing basis and emphasizes a deep understanding of the assisted subject. The platform contains motivation and structured explanations consisting of several sessions, followed by appreciation in the form of certificates.